The XMAP215 homologue Stu2 at yeast spindle pole bodies regulates microtubule dynamics and anchorage - Usui, Takeo (Oxford University Press, 2003)
The yeast protein Stu2 belongs to the XMAP215 family of conserved microtubule-binding proteins which regulate microtubule plus end dynamics. XMAP215-related proteins also bind to centrosomes and spindle pole bodies (SPBs) through proteins like the mammalian transforming acidic coiled coil protein TACC or the yeast Spc72. We show that yeast Spc72 has two distinct domains involved in microtubule organization. The essential 100 N-terminal amino acids of Spc72 interact directly with the γ-tubulin complex, and an adjacent non-essential domain of Spc72 mediates binding to Stu2. Through these domains, Spc72 brings Stu2 and the γ-tubulin complex together into a single complex. Manipulation of Spc72–Stu2 interaction at SPBs compromises the anchorage of astral microtubules at the SPB and surprisingly also influences the dynamics of microtubule plus ends. Permanently tethering Stu2 to SPBs by fusing it to a version of Spc72 that lacks the Stu2-binding site in part complements these defects in a manner which is dependent upon the microtubule-binding domain of Stu2. Thus, the SPB-associated Spc72–Stu2 complex plays a key role in regulating microtubule properties.